Sun's big splash [Niagara microprocessor chip]. - Geppert, L. (IEEE spectrum)
A new microprocessor chip was developed by Sun Microsystems Inc. that is intended for volume servers that are at the heart of data centers running the information and Web processing for businesses, universities, hospitals, factories, and the like. The new chip, called Niagara for the torrent of data and instructions that flow between the chip and its memory, was designed from the ground up to do away with the impact of latency - the idle time a microprocessor spends for data or instructions to arrive from memory. The goal of the design is to build a microprocessor that works 10 times as efficiently as existing devices for processing applications at half the power consumption of comparable devices. This paper discusses the development of the Niagara chip and its advantages from other microprocessors.